Teaching challenges of Social Studies in El Salvador - Flores, María Julia (2020)
This article proposes to reflect on the challenges of teaching Social Sciences in El Salvador. The proposal starts from the idea of what, how, and for what to teach; next, there is a need to promote new research spaces. It concludes by pointing out the desirability of making a textbook policy.